On Jacobsthal and Jacobsthal-Lucas hybrid numbers - Szynal-Liana, Anetta; Włoch, Iwona (Annales Mathematicae Silesianae, 2018)
The hybrid numbers are generalization of complex, hyperbolic and dual numbers. In this paper we consider special kinds of hybrid numbers, namely the Jacobsthal and the Jacobsthal-Lucas hybrid numbers and we give some their properties.